PENGARUH WORD OF MOUTH DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA STUDIO FOTO JUN MENGANTI, GRESIK - Muchammad Aji Ma’arif; Yuyun Widiastuti (Jurnal Ekonomi, Bisnis dan Social, 2024)
This study aims to examine and analyze the influence of Word of Mouth and Service Quality on Consumer Purchase Decisions. The unit of analysis in this study was Jun's Photo Studio consumers of 96 people. Samples were taken using Accidental Sampling. Data analysis was performed using statistics with SPSS tools. Based on the results of data analysis using the t test it is known that partially Word of Mouth and Service Quality have a positive and significant influence on Consumer Purchase Decisions. Meanwhile, based on the results of data analysis using the F test, it is known that simultaneously Word of Mouth and Service Quality have a positive and significant influence on Consumer Purchase Decisions.